Final technical report for equipment for basic research on turbulence mechanics of shear flow - Baldwin, Lionel V., author; Atesmen, Kemal M., author; Colorado State University, Department of Civil Engineering, publisher (Colorado State University. Libraries, 1970)
The experimental apparatus which has been constructed to study the mechanics of turbulent shear flow is described. The preliminary calibration experiments have been performed; the results are discussed. The apparatus meets all the specifications over the entire experimental range which was described in the original proposal for this grant.
CER70-71LVB-HMA42.
August, 1970.
National Science Foundation Project GK-10375.
Keywords: Flumes -- Hydrodynamics; Shear flow